Let's date in Namibia - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Since 1997, a government farm in Namibia has been laying the foundation for southern Africa s first commercial date production enterprise. Now 10,000 date palms, managed by 50 farmers, and free of major pests and diseases, drip-irrigated and...